Chess as a meaning: evolution of a significant in medieval culture - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2021)
Dedicated to the analysis of chess as a sign system (namely as meaning). The modelling nature of the chess game has been substantiated. The process of semiotic evolution of chess pieces game has been reconstructed: in this context chaturanga, chatrang, shatranji, Levis chess, lovers’ chess, courier chess, moon chess and others game have been analysed. The evolution of the meanings behind a chess game through the history of medieval culture has been considered: battle – knightly tournament – courtly flirting – society as a whole – being as such.
Keywords: sign system; model; signified; chess; chess pieces; hidden meanings; transformation of values; evolution of semantics